Use of Liposomal Bupivacaine in Pediatric Peripheral Nerve Blocks after Traumatic Amputation. (16th August 2021) - Halenda, Gregory M.; Voulgarelis, Stylianos
Abstract : Liposomal bupivacaine has been explored for indications in regional anesthesia, but little has been reported about its use in pediatric patients. In March 2021, the FDA approved an indication for liposomal bupivacaine as an infiltrated local anesthetic in children older than the age of six. Despite this recently expanded indication, the literature lacks reports of use for peripheral nerve blockade in children. We describe a case where liposomal bupivacaine was used for femoral and sciatic nerve blocks in a 5-year-old child with traumatic amputation of his lower leg. Pain control was excellent, with no pain or opioid use reported during the first 62 hours. After the regional anesthesia subsided, the patient required in total 4 oral doses of oxycodone 0.1 mg/kg prior to discharge. The patient did not develop chronic pain or phantom limb syndrome. While liposomal bupivacaine is not currently FDA-approved for peripheral nerve blockade in children, this case highlights a potentially effective use of this drug and possible area for further investigation.